The complete chloroplast genome sequence of Sorbus amabilis (Rosaceae). Issue 3 (2nd July 2020) - Zhang, Xingwang; Xie, Yanping; Xiao, Shuping; Wu, Xiaomin
Abstract: Sorbus amabilis Cheng ex Yü, a small excellent ornamental tree species, is only distributed in Eastern China. In this study, we assembled and annotated the complete chloroplast (cp) genome of the species using the next-generation sequencing for the first time. The cp genome was 160, 006 bp in size, consisting of two copies of invert repeat (IR) regions of 26, 405 bp, one large single-copy (LSC) region of 87, 870bp, and one small single-copy (SSC) region of 19, 326 bp. The overall GC content of the genome was 36.55%. The genome was predicted to contain 128 genes, including 88 protein-coding genes, 37 tRNA genes, and eight rRNA genes. Phylogenetic analysis of 25 chloroplast genomes in Rosaceae indicated that S . amabilis is most closely related to S . commixta . These findings may provide useful information to the phylogeny of the genus Sorbus .